Increasing transnational sea‐ice exchange in a changing Arctic Ocean. Issue 6 (27th June 2017) - Newton, Robert; Pfirman, Stephanie; Tremblay, Bruno; DeRepentigny, Patricia
Abstract : Abstract: The changing Arctic sea‐ice cover is likely to impact the trans‐border exchange of sea ice between the exclusive economic zones (EEZs) of the Arctic nations, affecting the risk of ice‐rafted contamination. We apply the Lagrangian Ice Tracking System (LITS) to identify sea‐ice formation events and track sea ice to its melt locations. Most ice (52%) melts within 100 km of where it is formed; ca. 21% escapes from its EEZ. Thus, most contaminants will be released within an ice parcel's originating EEZ, while material carried by over 1 00, 000 km 2 of ice—an area larger than France and Germany combined—will be released to other nations' waters. Between the periods 1988–1999 and 2000–2014, sea‐ice formation increased by ∼17% (roughly 6 million km 2 vs. 5 million km 2 annually). Melting peaks earlier; freeze‐up begins later; and the central Arctic Ocean is more prominent in both formation and melt in the later period. The total area of ice transported between EEZs increased, while transit times decreased: for example, Russian ice reached melt locations in other nations' EEZs an average of 46% faster while North American ice reached destinations in Eurasian waters an average of 37% faster. Increased trans‐border exchange is mainly a result of increased speed (∼14% per decade), allowing first‐year ice to escape the summer melt front, even as the front extends further north. Increased trans‐border exchange over shorter times is bringing the EEZs of the Arctic nations closer together, which should be taken into account in policy development—including establishment of marine‐protected areas. Plain Language Summary: We use data from satellite images to identify the formation, drift tracks, and melt locations of sea ice in the Arctic. Most ice melts locally: only about 21% is exported from the exclusive economic zone (EEZ) in which it is formed. That export is nonetheless about 1, 000, 000 km 2 each year. As the ice cover has thinned and the summer sea ice has retreated in a warming Arctic, formation and melt locations have moved further north, ice drifts have accelerated, and the area of ice formation and melt has increased. We looked at ice formation and transport between the EEZs of the Arctic nations, and broke the record into two periods: 1988–1999 and 2000–2014. As the Arctic warms, more ice is transported between EEZs and it is arriving at the receiving EEZ faster, than in the past. Between the two study periods: Sea ice velocity increased by about 14%/decade; Russian ice reached melt locations in other nations' EEZs 46% faster; and North American ice reached Eurasian destinations 37% faster. Exchanges of ice have increased as a result. For example, export of ice from Russia to Norway increased by 11% and export from Alaska to Russia by 16%. Key Points: Ca. half of Arctic sea‐ice melts within 100 km of formation, while ca. one fifth melts in a different nation's exclusive economic zone Over the past ca. 30 years, sea‐ice drift speeds have increased and transit times decreased between remote parts of the continental shelf Exchange of sea ice and ice‐rafted material between waters of the Arctic nations has likely increased over the past approximately 30 years.